2020
DOI: 10.1055/s-0040-1710512
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Newborns and Infants—Low Risk of Severe Disease: Silver Lining or Dark Cloud?

Abstract: One hundred years after the 1918 influenza pandemic, we now face another pandemic with the severe acute respiratory syndrome–novel coronavirus-2 (SARS-CoV-2). There is considerable variability in the incidence of infection and severe disease following exposure to SARS-CoV-2. Data from China and the United States suggest a low prevalence of neonates, infants, and children, with those affected not suffering from severe disease. In this article, we speculate different theories why this novel agent is sparing neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(82 citation statements)
references
References 33 publications
1
73
0
8
Order By: Relevance
“…50 Rawat et al speculate on why neonates have been spared of COVID-19 serious symptomatology, but also caution that they can be carriers for transmission of the virus to vulnerable adults. 55 In addition to that, there is scarce information about the short-and long-term effects of infection on neonates. Therefore, it is vital to prevent infection in the neonates.…”
Section: Discussionmentioning
confidence: 99%
“…50 Rawat et al speculate on why neonates have been spared of COVID-19 serious symptomatology, but also caution that they can be carriers for transmission of the virus to vulnerable adults. 55 In addition to that, there is scarce information about the short-and long-term effects of infection on neonates. Therefore, it is vital to prevent infection in the neonates.…”
Section: Discussionmentioning
confidence: 99%
“…In adults with severe respiratory failure from SARS-CoV-2 infection, who typically experience clinical deterioration about 1 week following illness onset, a dysregulated immune system is thought to drive disease manifestations, as opposed to direct cellular injury from viral infection (Stage II-pulmonary phase). Children appear to have less severe pulmonary manifestations compared to adults, possibly due to lower gene expression of the angiotensin converting enzyme (ACE)-2 receptor (the target of SARS-CoV-2) [12,13]. Immune dysregulation in adults with respiratory disease is characterized by lymphopenia (specifically NK cells, CD4 T lymphocytes and B lymphocytes) and sustained production of pro-inflammatory cytokines, such as tumor necrosis factor (TNF)-α and interleukin (IL)-6 [14].…”
Section: Relationship Of Mis-c To Covid-19 and Pathogenesismentioning
confidence: 99%
“…In this view, a previous “contact” with these viruses might provide at least a partial/basal immunization (through the production of neutralizing antibodies) shielding humans also against the circulating SARS-CoV-2. Recently, other authors have agreed with this hypothesis in which a cross-immunity can be induced by seasonal infections by human coronaviruses especially in children [9] , [21] , [22] . This may explain their modest involvement both in the number and severity of the infection.…”
Section: Consequences Of the Hypothesis And Discussionmentioning
confidence: 73%
“…Another possibility may be related to higher numbers of CD4 cells (due to the thymus activity) and to lower numbers of CD8 T lymphocytes in children compared to adults [3] , [9] . This may be protective because it has been reported that SARS-CoV-2 infection is related to a decrease in CD4 cells in older men when compared with younger men and women’s higher CD4 cell numbers [3] .…”
Section: Introductionmentioning
confidence: 99%